VIRTUAL REALITY PORTAL RUMAH BERBASIS ANDROID - Wafiah, Andi; Wakkang, Hamka; Arwandi, Arya (Fakultas Teknik Universitas Muhammadiyah Parepare, 2022)
The house is a building that is used as a place to live for a certain period of time and as a primary human need, in a special sense the house refers to social concepts that are interwoven in the place of residence, such as resting, eating, sleeping, and doing activities. The more modern and the more sophisticated the technology, as for the way that entrepreneurs can do that, namely using virtual reality, with the implementation of virtual reality, consumers do not need to leave the house to see what the property company has to offer, just through their smartphone they can now see what is offered and You can also see 3D visuals, such as room layouts, and interiors that have been created. The results achieved in this research are with the application of Virtual Reality Portal Home Based on Android at PT Kelapa Gading Berlian, the public can now see what is offered and can also see 3D visual displays, such as room layouts, and interiors that have been made with using virtual technology